Synthesis and characterization of bioceramic oxide coating on Zr-Ti-Cu-Ni-Be BMG by electro discharge process - Aliyu, A.âA.A. (Pleiades Publishing, 2019)
In its native state, Zr-Ti-Cu-Ni-Be bulk metallic glass (BMG) do not allow strong physical bonding to the surrounding tissues when implanted, due to its inherent low strength bioinert oxide surface. In this study, a bioceramic oxides and strong carbide coating are synthesized on the Zr-Ti-Cu-Ni-Be surface, by electro-discharge coating (EDC) technique. This coating is expected to enhance cell adhesion and cell proliferation of the Zr-based BMG material as a potential implant. The influence of various hydroxyapatite (HA) powder concentrations added to the dielectric fluid on the treated BMG specimens, have been investigated. Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDX), X-ray Diffraction (XRD) characterization techniques was employed to study the phases, morphology and thickness of the electro-discharge coated Zr-based BMG. The FESEM and the XRD analysis revealed the coating formation of about 34.0 Âµm thick, containing nanoporous bioceramic oxides (CaZrO2, ZrO2, HA) and hard carbides (ZrC, TiC) on the substrate surface. The EDX spectrum confirmed the high deposition of some HA alloying elements (Ca, O, P), with calcium almost equal in proportion to that of zirconium. A high material deposition rate of 0.015267 g/min at the optimum parameters setting of Dc = 8 A, Dt = 8 Âµs, Pc = 15 g/L and Ep = âVe was achieved. Â© Springer Nature Switzerland AG 2019.